Student Motivation and Learning Strategies of Students from USA, China and Bangladesh - Quamrul H Mazumder (International Journal of Evaluation and Research in Education (IJERE), 2014)
To better understand the motivation and strategies used by students around the world, a comparative study among three different countries was performed.The current study used the Motivated Strategies for Learning Questionnaire (MSLQ) questionnaire to collect responses from students in public and private universities of Bangladesh.The results were also used to compare the differences between public and private universities of Bangladesh, as there is a national debate on the quality of these two types of universities in Bangladesh.The number of students that participated in this study was 164 with 143 from private universities and 21 from public universities. The number of lower responses from public universities may be an indicator of their lack of motivation to participate in this study. MSLQ questionnaires have been used and adapted by universities across the world as a valid instrument to measure the level of motivation and the learning process.The survey consists of 18 questions to evaluate motivation and learning strategies. The results of the responses from Bangladesh were compared with a previous study between students of USA and China [9].There was no significant difference between public and private universities in Bangladesh in most of the categories.However, some differences were observed among these three countries indicating that students from different geographical regions may have different levels of motivation and learn differently.DOI: http://doi.org/10.11591/ijere.v3i4.6288